Design, construction, verification and testing of a low cost germinator: Germinador de bajo costo - Hernández López, Alejandro; Avila Alejandre, Alma Xochil; Mendoza Ambrosio, Francisco Noe; López, Héctor Hernández (Revista Mexicana de Ciencias Agrícolas, 2019)
Automated germinators are an indispensable tool to optimize agricultural processes. However, they have high costs, so the design, construction and operation of devices with accessible prices for small producers is required. The objective of this work was to design, build and verify a prototype of low cost germinator, under the guidelines of a prototype design. Said germinator was built using materials available in the region and is able to automatically control the temperature and photoperiod through circuits W1401 and Tem-8 48386 respectively. Furthermore, by means of simple switches, the light intensity can be controlled. Additionally, a temperature verifier was built with an Arduino Uno card. The verification system allowed the monitoring of temperature changes in real time (every minute). The prototype was tested by germinating seeds of Capsicum chinense, using different volumes of imbibition water. According to the results obtained, the built prototype is adjusted to the requirements recommended by the International seed testing association (ISTA), as well as by the Food and Agriculture Organization (FAO) for the evaluation of seeds, but also showed a higher yield, compared to a commercial incubator and even a very minor construction and operation cost.
Keywords: arduino; germination; low cost